Population peculiarities found in the prevalence of chronic diseases of ear, nose and throat in rural adults in Khakass Republic - V. A. Kishteyeva; T. A. Kapustina; G. I. Burenkov (Бюллетень сибирской медицины, 2009)
The article shows the indices of prevalence and structure in chronic othorhinolaryngologic pathology in rural native and alien people of Khakass Republic. The authors examined 2 023 subjects by random. The results of cross-section research revealed high prevalence of the pathology in Ear-Nose-Throat-organs in rural population of the republic irrespective of ethnic belonging. Comparative analysis of prevalence indices corresponding to the Europoids and the Khakasses determined the range of ethnic peculiarities in epidemiology of chronic diseases of ear, nose and throat.